Kreativitas dalam Membina Kedisiplinan Santri pada Masa Pandemi Covid-19 - Muhammad, Hasman Zhafiri; Wildan, Syakur (Lembaga Yasin AlSys, 2023)
Human life cannot be separated from the existence of a rule of life. The rules of life make human beings more directed and organized in accordance with the discipline applied. Thus, man is required to obey the rules or it can be said to live a disciplined life in accordance with the values or norms prevailing in his life. The discipline that exists in the students of MANPK Yogyakarta, has been organized and carried out properly. The existence of good implementation cannot be separated from the role of creativity of a coach in accompanying and escorting the discipline of students. With this background, the researcher raised the title of Coach Creativity in the Formation of Santri Discipline at MANPK Yogyakarta During the Covid-19 Pandemic. The purpose of this study is to find out and describe the form of creativity of coaches in shaping the discipline of students at MANPK MAN 1 Yogyakarta. This type of research is descriptive qualitative research. Type of qualitative research, which is research that aims to describe fully and in depth the social reality and various phenomena that occur so that the characteristics, characters, traits, and models of these phenomena appear. The results showed that first, the discipline that exists in the students of MANPK Yogyakarta is good, although there are some students who have not carried out the rules properly. The two creativity that exists in the coach in shaping the discipline of students include by making a joint order between students and coaches (MANPK policy makers), the second way is control carried out by the coach with parents to accompany the discipline of students, the third way by example, where exemplary can provide an example for student discipline, the fourth way with a personal approach, where to discipline students, it is necessary to have personal communication between coaches and students.